AN EXAMINATION OF THE NATURE AND IMPLICATION OF THE MEDICAL CONCEPT OF DEATH IN RELATION TO LAW - Francis, Toluwani Mercy (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
For a very long time, the absence of an established uniform definition of death created uncertainty and put physicians, including relatives and friends of patients and the society at large, in acute dilemma. This paper examined the nature and implication of the medical concept of death in relation to law. This research is doctrinal, both primary and secondary sources of law were relied on. The former includes statutes and cases while the latter consist of books, journal articles, news articles and other materials from the internet. This study found that the American Bar Association, the American Medical Association and the National Conference of Commissioners endorsed definition of death on Uniform State Laws has not been totally effective in addressing matters arising from recent developments in medical treatments such as artificial support systems, organ donation and transplantation, human medical research, euthanasia, genetic engineering, living wills, death certification rules, the maintenance of life support beyond brain death for pregnant women/organ donors, protection of corpses etc. as each has its own distinct ethical and legal considerations. This study also found that there is a beautiful and dutiful interconnection between Medicine and Law on the subject of death. This study concluded that there exist certain legal, medical and ethical issues which should be considered in the process of determining death. Medical practitioners must be aware of these considerations to prevent the continuous violation of the constitutional right to life of patients.